Pengaruh Pandemi COVID-19 Terhadap Minat dan Niat Pariwisata Di Jawa Timur - Hurian Kamela; Ryan Saputra Alam; Elif Pardiansyah (Universitas Sultan Ageng Tirtayasa, 2021)
COVID-19 is a serious pandemics that affects life survival, including in Indonesia. One of the affected areas in East Java Province, especially in the tourism sector. This study aimed to quantitatively measure the interest of the East Java people towards tourism intentions and interests based on the Theory Of Planned Behavior (TPB). The research method used is a questionnaire with 102 people who reside in East Java. The research period is one month, beginning from September 2020 (during the COVID-19 pandemic). The dependent variable used is the intention, and the independent variable is Attitude toward the behavior, Subjective norm, Perceived behavioral control, Anticipated regret. This study proves that only Attitude toward the behavior and Perceived behavioral control has a positive effect on tourism interests and intentions of the people of East Java. These results provide information that there is still severe public concern about a pandemic. However, the government can encourage tourism because, based on the research results, there is still a public interest in choosing a vacation, either on nature vacation or enjoying seaside.